2018
DOI: 10.2139/ssrn.3250383
|View full text |Cite
|
Sign up to set email alerts
|

A Storm in an IoT Cup: The Emergence of Cyber-Physical Social Machines

Abstract: The concept of 'social machines' is increasingly being used to characterise various socio-cognitive spaces on the Web. Social machines are human collectives using networked digital technology which initiate real-world processes and activities including human communication, interactions and knowledge creation. As such, they continuously emerge and fade on the Web. The relationship between humans and machines is made more complex by the adoption of Internet of Things (IoT) sensors and devices. The scale, automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This needs task-specific human machine interfaces [44], for self-aware machines and component prognostics and health management [45].…”
Section: Life Cycle and Anti-counterfeit For Artificial Intelligence mentioning
confidence: 99%
“…This needs task-specific human machine interfaces [44], for self-aware machines and component prognostics and health management [45].…”
Section: Life Cycle and Anti-counterfeit For Artificial Intelligence mentioning
confidence: 99%
“…The development of such cognitive engine and its application, would undoubtedly bring multiple benefits and would enable deeper understanding of the impact of cyber risk at the edge. Nonetheless, IoT networks represent complex coupled systems (D. De Roure et al 2019), that can be described as cyber-physical social machines (Madaan et al 2018) and social machines (David De Roure et al 2015) should be observed in practice (Shadbolt et al 2019). Given that IoT is considered as critical enabler (Lee et al 2019a) of value creation (Lee et al 2019b), the findings of this study would probably be best verified when observed in practice.…”
Section: Resultsmentioning
confidence: 65%
“…However, the AI/ML infrastructure in the communications network and the relevant cyber security technology must evolve in an ethical manner that humans can understand, while maintaining maximum trust and privacy of the users. IoT networks represent complex coupled systems [40], that can be described as cyber-physical social machines [41] and social machines [42] should be observed in practice [43]. Given that IoT is considered as critical enabler [44] of value creation [45], the findings of this study would probably be best verified when observed in practice.…”
Section: Resultsmentioning
confidence: 83%